DEMO design activity in Europe: Progress and updates - Federici, G.; Bachmann, C.; Barucca, L.; Biel, W.; Boccaccini, L.; Brown, R.; Bustreo, C.; Ciattaglia, S.; Cismondi, F.; Coleman, M.; Corato, V.; Day, C.; et al. (Fusion engineering and design, 2018)
This paper describes the progress of the DEMO Design Activities in Europe and particularly the work done to address critical design integration issues that affect the machine configuration and performance, the plant concept layout and the selection of system design and technologies. Work continues to be primarily focused on the design integration of a pulsed baseline DEMO reactor concept, but a number of alternative configurations (e.g., a double-null divertor and a snowflake divertor as well as a ‘flexi’ DEMO that operates initially in an inductively driven pulsed regime, with the possibility to be upgraded to a long-pulse or steady-state machine with a greater reliance on auxiliary current drive, etc.) are under preliminary study, especially to evaluate their DEMO reactor relevance. Some initial considerations are given on the strategy to implement a structured design and technology down-selection, that progressively reviews and narrows options to arrive at the DEMO plant concept that addresses major system integration risks and offers the best probability to satisfy all stakeholder mission requirements. Finally, some recent technical achievements are highlighted.